Assessment of Selected Overdose Poisoning Indicators in Health Care Administrative Data in 4 States, 2012. (July 2017) - Hume, Beth; Gabella, Barbara; Hathaway, Jeanne; Proescholdbell, Scott; Sneddon, Cristy; Brutsch, Elizabeth; Hedin, Riley; Drucker, Christopher J.
Objectives: In 2012, a consensus document was developed on drug overdose poisoning definitions. We took the opportunity to apply these new definitions to health care administrative data in 4 states. Our objective was to calculate and compare drug (particularly opioid) poisoning rates in these 4 states for 4 selected Injury Surveillance Workgroup 7 (ISW7) drug poisoning indicators, using 2 ISW7 surveillance definitions, Option A and Option B. We also identified factors related to the health care administrative data used by each state that might contribute to poisoning rate variations. Methods: We used state-level hospital and emergency department (ED) discharge data to calculate age-adjusted rates for 4 drug poisoning indicators (acute drug poisonings, acute opioid poisonings, acute opioid analgesic poisonings, and acute or chronic opioid poisonings) using just the principal diagnosis or first-listed external cause-of-injury fields (Option A) or using all diagnosis or external cause-of-injury fields (Option B). We also calculated the high-to-low poisoning rate ratios to measure rate variations. Results: The average poisoning rates per 100 000 population for the 4 ISW7 poisoning indicators ranged from 11.2 to 216.4 (ED) and from 14.2 to 212.8 (hospital). For each indicator, ED rates were usually higher than were hospital rates. High-to-low rate ratios between states were lowest for the acute drug poisoning indicator (range, 1.5-1.6). Factors potentially contributing to rate variations included administrative data structure, accessibility, and submission regulations. Conclusions: The ISW7 Option B surveillance definition is needed to fully capture the state burden of opioid poisonings. Efforts to control for factors related to administrative data, standardize data sources on a national level, and improve data source accessibility for state health departments would improve the accuracy of drug poisoning surveillance.